Energy Calibration and Inverse-Square Law of Radiation in Gamma-Ray Measurement Using a Scintillation Detector for Laboratory Experiments - Shiori Iida; Wei-Guo Jin (Journal of Engineering, 2023)
Over the past two years, third-year undergraduate students from Toho University’s Department of Physics conducted laboratory experiments on gamma-ray measurement using a scintillation detector. Approximately, 30 experimental data points were collected and subsequently analyzed. The analysis focused on the energy calibration method and the inverse-square law of radiation. Results revealed that employing quadratic or cubic function fits for energy calibration yielded more than twice the accuracy compared to the conventional linear function fit. Regarding the deviation from the inverse-square law of radiation, a correction method utilizing a correction parameter was compared with a power function fit method. The discussion encompassed the correction parameter and the exponent of the power function.